The EFL Students’ Preference: English Books or Instagram Posts - Rini Nurul Amla; Santiara Santiara; Mela Monita; Rahayu Atila; Rena Juliana (Universitas Serambi Mekkah, 2020)
The purpose of this study is to find out whether or not English students of The University of Serambi Mekkah preferred learning English throughsocial media or printed media. This study was conducted by comparing anobject from media, such as Instagram posts and English books. Thisstudy used descriptive design. The sample consisted of 30 Englishstudents of the University of Serambi Mekkah. The instrument wasquestionnaire, and the percentage formula was used for data analysis.The result showed that the students preferred learning English throughEnglish books (68%) to instagram posts (55, 33%). Therefore, it isrecommended that the university adds more English books in the libraryto assist the students in learning.